Assessment of salivary thiocyanate levels and pH in the saliva of smokers and nonsmokers with chronic periodontitis - A comparative study - C Naresh Kumar; Subramaniam M Rao; Ankur Jethlia; Chandra Shekhar Linganna; Manish Bhargava; Devendra H Palve (Wolters Kluwer Medknow Publications, 2021)
Background: It has been speculated that the pathogenesis of diseases prompted by cigarette smoking includes oxidative damage by free radicals. Though, definitive evidence that smoking may cause the oxidative modification of target molecules in vivo is lacking. Therefore, the purpose of this study was to estimate and compare the levels of salivary Thiocyanate (SCN) and power of hydrogen (pH) in the saliva of smokers and nonsmokers with chronic periodontitis (ChP). Materials and Methods: A study population consisted of 60 male systemically healthy subjects in the age group of 20-65 years that was further divided into three groups: Group 1: 20 Healthy nonsmokers, who never smoked. Group 2: 20 nonsmokers with chronic periodontitis. Group 3: 20 smokers with chronic periodontitis. Unstimulated saliva was collected for at least 5 mins and clinical parameters; salivary pH and SCN thiocyanate levels were assessed using the spectrophotometric method. Statistical analysis was performed using SPSS Inc 21.0, Chicago, II, United States of America. Results: Data showed that the mean salivary SCN level, periodontal parameters were higher in smokers with chronic periodontitis as compared to nonsmokers with chronic periodontitis and healthy subjects (P < 0.05.) Post Hoc tests multiple comparisons Tukey Honest Significant Difference (HSD) among three groups were statistically significant (p < 0.05). Conclusion: Salivary thiocyanate levels remain increased by smoking in addition to the impact of periodontitis, and these results also indicated a significant change in the pH depending on the severity of the periodontal condition in smokers. Thus, the measurement of salivary thiocyanate may prove to be useful in the early detection of periodontal disease. The salivary pH shows significant changes and, consequently, relevant to the severity of the periodontal disease. Salivary pH may thus be used as a quick chairside diagnostic biomarker.